Philosophies of race and ethnicity - Osborne, Peter; Sandford, Stella (Continuum, 2002)
Race and ethnicity have become two of the most loaded and contested concepts in the contemporary world. Philosophies of Race and Ethnicity aims to disentangle this complexity and guide the reader to a clearer understanding of the debates.Analysing the genealogy, meanings and political uses of the concepts of race and ethnicity, Philosophies of Race and Ethnicity draws on the best scholarship from philosophy, history, post-colonial studies, political theory and literary studies to explore the structure, status and scope of these concepts.Contributors: Linda Martin Alcoff, Chetan Bhatt, Rey Chow, Rebecca Karl, David Macey, Naoki Sakai, Bill Schwarz, Denise da Silva, Francoise Verges, Robert J. C. Young